2020
DOI: 10.1111/hel.12727
|View full text |Cite
|
Sign up to set email alerts
|

A panel of stomach‐specific biomarkers (GastroPanel®) for the diagnosis of atrophic gastritis: A prospective, multicenter study in a low gastric cancer incidence area

Abstract: Background Analysis of serum biomarkers for the assessment of atrophic gastritis (AG), considered as gastric precancerous lesion, is of growing interest and recommended by current guidelines. Our aim was to evaluate the diagnostic performance of a panel of biomarkers (GastroPanel®) for the detection of AG in France, a country of a low gastric cancer (GC) incidence. Material and Methods In this prospective, multicenter, cross‐sectional study, consecutive patients considered at increased risk of GC and undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 36 publications
(84 reference statements)
4
19
0
Order By: Relevance
“…However, in our study, the median serum gastrin level following the administration of vonoprazan (20 mg) for 4 weeks was 2,470 pg/mL, which is similar to the level in a previous report by Iwakiri et al [22]. Thus, patients may experience a sharp increase in the serum In recent years, Western countries have demonstrated that the serum level of G17, which is secreted from the antral G cells, has been used to evaluate the topography of gastritis by GastroPanel [23][24][25][26]. However, in Japan, the serum titer of gastrin has been used for the evaluation of corpus atrophy, and total gastrin is evaluated using the domestic enzyme-linked immunosorbent assay system.…”
Section: Discussionsupporting
confidence: 83%
“…However, in our study, the median serum gastrin level following the administration of vonoprazan (20 mg) for 4 weeks was 2,470 pg/mL, which is similar to the level in a previous report by Iwakiri et al [22]. Thus, patients may experience a sharp increase in the serum In recent years, Western countries have demonstrated that the serum level of G17, which is secreted from the antral G cells, has been used to evaluate the topography of gastritis by GastroPanel [23][24][25][26]. However, in Japan, the serum titer of gastrin has been used for the evaluation of corpus atrophy, and total gastrin is evaluated using the domestic enzyme-linked immunosorbent assay system.…”
Section: Discussionsupporting
confidence: 83%
“…( 59 61 ) Though follow-up endoscopy for Updated Sydney System to evaluate atrophic gastritis in the current study is prerequisite, the analysis of serum biomarkers for the assessment of CAG using stomach-specific diagnostic performance of GastroPanel ® was done. ( 62 64 ) As seen in Supplemental Fig. 3 * , the detection of corpus CAG and severe CAG was significantly improved in group taken 10 weeks of fermented kimchi relevant to gut microbiota changes.…”
Section: Discussionmentioning
confidence: 68%
“…This theory is supported by a group of French researchers who claim that GastroPanel has an insufficient diagnostic performance in case of mild gastric atrophy. However, it can be useful in selected groups of patients at high risk for gastric cancer, in particular to detect severe atrophy and corpus atrophy ( 29 ).…”
Section: Discussionmentioning
confidence: 99%